Atypical Small Acinar Proliferation: Repeat Biopsy and Detection of High Grade Prostate Cancer. (14th September 2015) - Leone, Andrew; Rotker, Katherine; Butler, Christi; Mega, Anthony; Li, Jianhong; Amin, Ali; Schiff, Stephen F.; Pareek, Gyan; Golijanin, Dragan; Renzulli, Joseph F.
Abstract : Purpose . Atypical small acinar proliferation (ASAP) is diagnosed in 1-2% of prostate biopsies. 30–40% of patients with ASAP may be diagnosed with prostate cancer (PCa) on repeat biopsy. Our objective was to examine the association between ASAP and subsequent diagnosis of intermediate/high risk PCa. Materials and Methods . Ninety-six patients who underwent prostate biopsy from 2000 to 2013 and were diagnosed with ASAP were identified. Clinicopathologic features were analyzed. Comparison was made between those with subsequent PCa on repeat biopsy and those with benign repeat pathology. Results . 56/96 (58%) patients had a repeat biopsy. 22/56 (39%) were subsequently diagnosed with PCa. There was no significant difference in patients' characteristics. Presence of HGPIN on initial biopsy was associated with a benign repeat biopsy (68% versus 23%). 17/22 (77%) had Gleason grade (GG) 3+3 disease and only 5/22 (23%) had GG 3+4 disease. Conclusions . 22/56 patients (39%) of patients who underwent a subsequent prostate biopsy following a diagnosis of ASAP were found to have PCa. 77% of these men were diagnosed with GG 3+3 PCa. Only 23% were found to have intermediate risk PCa and no high risk PCa was identified. Immediate repeat prostate biopsy in patients diagnosed with ASAP may be safely delayed. A multi-institutional cohort is being analyzed.